(untitled) (Sociologisk Forskning, 2025)
This study explores narrative identity through a qualitative analysis of joint interviews with parents and their children in a rural part of Sweden. The aim is to examine how parents construct narratives about themselves and how this narrativity is expressed in interaction with their children. Eleven lower secondary school children, together with one or two of their parents, were asked to discuss occupational choice and geographical mobility amongst themselves. The results illustrate that while parents tend to emphasize individual self-determination and the importance of not interfering with how their children shape their life course, their own storytelling functions as a vehicle for communicating values, social expectations, and moralizing themes. Utilizing an interactionist approach to Paul Ricoeur’s theory of narrative identity – particularly the notion of emplotment – the study examines how plots, characters, and other narrative elements of identity, are negotiated, modified, and co-produced in social interaction. The intergenerational negotiation of stories emerges as a process that not only explains the past but also might shape young subjects’ self-understanding and orientation toward the future.